Functionalization of aldehydes via N-heterocyclic carbene and base organic catalysts - Yang, Ruojie (Nanyang Technological University, 2014)
In this thesis, direct and efficient functionalization of aldehydes with organocatalysts towards synthetic attractive molecules is presented. Chapter II describes the direct α-functionalization of simple aldehydes under oxidative NHC catalysis and the direct generation of ester enolates by using simple nonfunctionalized aldehydes as substrates. The same transformation with only catalytic amount of quinone-derived oxidant can be realized by using much cheaper terminal oxidants MnO2, providing an economic solution for large scale industrial synthesis. Chapter III presents the [3+2] annulations of isatin and β-branched